PENGGUNAAN MEDIA AUGMENTED REALITY BERBASIS ANDROID DALAM PEMBELAJARAN TATA SURYA - Ridwan, Muhammad; Djudin, Tomo; Arsyid, Syaiful B. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to determine the effect of using Android-basedmedia augmented in solar system learning at the SMP Negeri 3 TelukKeramat. This research took an experiment format using a one-grouppretest-posttest design. The population in this study comprised fiveclasses, with a total of 162 students. Sampling was carried out in anintact group, and the sample in this research was Class VII Estudents, totaling 32 people. The instrument used was a learningoutcome test consisting of five multiple-choice and five essayquestions. The results of the data analysis showed that the averagescores of the student learning outcomes for the pre-test and post-testwere 61 and 73.3, respectively. Wilcoxon test results, where theresults of asymp.sig 0.000 lt; 0.5 and the effect size test results wereobtained at 1.68, which are included in the high category. Based onthis analysis, it is known that there are differences in student learningoutcomes before and after using AR augmented reality media. Thesemedia have a strong impact on student learning outcomes, making itpossible and effective to use augmented reality to improve studentlearning outcomes.